HUBUNGAN ANTARA KLASIFIKASI STROKE DENGAN GANGGUAN FUNGSI KOGNITIF PADA PASIEN STROKE - Dewi Nopia; Zaqyyah Huzaifah (Journal of Nursing Invention, 2020)
Stroke is the second leading cause of death in the world. Stroke is a vascular disorder caused by blockage or rupture of blood vessels in the brain, as a result of these conditions arises a clinical disorder resulting from damage to brain cells in certain parts. Symptoms can disrupt the process of mental activity or sublime cortical function including cognitive function. This study aims to determine the relationship between stroke classification with cognitive impairment in stroke patients. This type of research used in this study is a correlation analysis, with a cross-sectional design, a sample of 36 respondents according to criteria, using Chi-Square at α = 0.05. There is a relationship between the classification of stroke with cognitive impairment in stroke patients with a value of ρ value = 0,000. Penyakit stroke merupakan penyebab kedua kematian di dunia. Stroke merupakan gangguan vaskular yang disebabkan oleh sumbatan atau pecahnya pembuluh darah diotak, akibat dari keadaan tersebut timbul suatu kelainan klinis akibat dari kerusakan sel otak pada bagian tertentu. Gejala dapat terganggunya proses aktifitas mental atau fungsi kortilal luhur termasuk fungsi kognitif. Penelitian ini bertujuan mengetahui hubungan antara klasifikasi stroke dengan gangguan fungsi kognitif pada pasien stroke. Jenis penelitian yang digunakan dalam penelitian ini adalah analisa korelasi, dengan rancangan cross-sectional, sampel 36 responden sesuai dengan kriteria, menggunakan Chi Square pada α = 0,05. Ada hubungan antara klasifikasi stroke dengan gangguan fungsi kognitif pada pasien stroke dengan nilai ρ value = 0,000.